The key drivers of employee engagement in organisations amid COVID-19 era - Niu, Sihan (2022)
Due to the worldwide uncertainty caused by the Covid-19 pandemic, it is more important than ever for organisations to further manage employee engagement in order to increase productivity (Jacob and Julia 2021). However, during special times, there are many employees who are required to work remotely or from home for long periods of time, which leads to a lot of uncertainty and stress and negatively affects employee engagement. Therefore, it is crucial for organisations to maintain employee engagement by using organisational practices and drivers related to employee engagement during the period when COVID-19 is still in place (Chanana 2021).